Cartographic image of Samogitia in the old maps of Lithuania, Poland and other neighboring countries (1231–1700) - Lukoševičius, Viktoras (Geodesy and Cartography, 2014)
While continuing researches on ancient cartography (Lukoševičius 2013a, 2013b) the publication is aimed at viewing maps of Samogitia in the perspective of historical events, with a special emphasis on most important historical events as well as cartography development moments. The method used is analysis the most representitive examples of maps, by different authors, found in cartographical archives. The article presents the authors and designers over 45 maps where Samogitia is marked and discusses map characteristics. It also provides links that are helpful for the readers interested in a more detailed studies of specific maps. Such presentation should help revise and complete the historical image of Samogitia because the old maps were not specific to any one topic. They – the universal, they were reflected in both the natural and social phenomena and the evolution of patterns. It was also available and various historical comments. Often, the old maps are often associated with military needs. Summarizing research results the author conclude that presented ancient maps is important for the history of Lithuania cartography and are true historical witnesses helping to understand long and complicated formation process of Samogitia and the state of Lithuania; however the analysis alone is insufficient to fully reveal its historic concept.